Respons Pertumbuhan Kelor (Moringa oleifera)Terhadap Pemberian Unsur Hara Fermentasi Cair Limbah Kulit Nanas (Ananas comosus L.) - Nela Rossa Damayanti; Dian Mutiara; Dewi Novianti (Universitas PGRI Palembang, 2022)
Research on the Growth Response of Moringa (Moringa oliefera L.) to the Administration of Liquid fermentation Nutrients from Pineapple Peel Waste (Ananas comosus L.) aims to examine the appropriate dosage of liquid fermentation nutrients from pineapple peel waste to Moringa plants carried out from April to June. 2021 at the Workshop of the Faculty of Science and Technology, Universitas PGRI Palembang. The study used RAL, namely the administration of liquid fermentation nutrients from pineapple peel waste which consisted of 6 treatments, 4 replications of giving liquid organic nutrients from pineapple peel waste, namely P0 (without liquid nutrients), P1 (300 ml of liquid nutrients), P2 (400 ml of liquid nutrients). liquid nutrients), P3 (500 ml of liquid nutrients), P4 (600 ml of liquid nutrients), P5 (700 ml of liquid nutrients). The results of the research on the Growth Response of Moringa (Moringa oliefera l.) to the Administration of Liquid fermentation Nutrients from Pineapple Peel Waste (Ananas comosus L.) showed that the application of nutrients from pineapple peel waste had an effect on the growth of Moringa. The P5 treatment yielded results on plant height, number of leaves of Moringa, while the lowest average value was found in P0 treatment.Keywords: Growth, Moringa, nutrients, pineapple peel waste